Double Prefixes in Kakenauwe Language - La Ino (Masyarakat Linguistik Indonesia Universitas Andalas, 2020)
The article discusses the double prefix of the Kakenauwe language. This language is spoken in the Kapuntori sub-district and the Lasalimu sub-district in Buton district. This research uses a qualitative approach with descriptive methods. The descriptive method used in this research method is mainly dealing directly with data collection. The data used in this study is oral language data. The results obtained from the analysis of the data are the thirty-three three prefixes of the Kakenauwe language, cifo-, cifopo-, feka-, fomo-, fose-, cafÃ©-, kafeka-, kafo-, nacifo-, nako-, namo-, nocifo-, nefo- pofeka-. The Kakenauwe language has specific criticisms such as the kakenauwe language, which is a vocalist language, which has double prefixes up to three times.